Evaluation of the pharmacokinetics, tissue distribution and excretion studies of YMR-65, a tubulin polymerization inhibitor with potential anticancer activity, in rats using UPLC-MS/MS. (2nd September 2018) - Fan, Ali; Zhang, Yaliang; Zhang, Qing; Wei, Jiali; Lu, Xiaoyu; Ren, Guanghui; Zhao, Di; Li, Ning; Zhu, Hailiang; Chen, Xijing
Abstract: 1. YMR-65, 5-(5-bromo-1-methyl-1H-indol-3-yl)-3-(3-methoxyphenyl)-4, 5-dihydro-1H-pyrazole-1-carboxamide, is a new tubulin polymerization inhibitor with encouraging anticancer activity. 2. The validated ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS) method was successfully applied to the pharmacokinetics, tissue distribution and excretion study of YMR-65 after oral and intravenous administration. The area under concentration-time curve (AUC0-∞ ) for YMR-65 were 151.67 ± 54.48 and 459.45 ± 49.23 ng/ml*h for oral and intravenous administration at the dosage of 1.5 mg/kg, respectively and the oral bioavailability was about 33.01%. Moreover, YMR-65 was extensively distributed in heart, liver, spleen, lung, kidney, stomach, intestine and testis and the highest were detected in heart, followed by stomach, intestine and liver. The majority of YMR-65 was excreted via feces and its accumulative excretion ratio during the period of 96 h was 19.83 ± 3.01%, but only 1.54 ± 0.37 and 0.215 ± 0.026% for urine within 96 h and bile within 10 h after intravenous administration, respectively, though the fecal and urine excretion were incomplete within 96 h. 3. In summary, this study defined the pharmacokinetic characteristics of YMR-65 in vivo and the important data can be a useful resource for further research and development.